(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
This study examines the relationship between wage structure, employee welfare, and job satisfaction in community colleges of Bagmati Province. By integrating key compensation theories, including equity theory, Herzberg’s Two-Factor Theory, and Expectancy Theory, the research explores how wage disparities impact employee motivation, retention, and institutional efficiency. A mixed-methods approach was employed, utilizing surveys, interviews, and statistical analyses such as the Chi-Square Test and Karl Pearson’s Coefficient of Correlation to assess the significance of wage structures in shaping employee well-being. The findings indicate a strong correlation between comprehensive welfare measures and job satisfaction, emphasizing the need for equitable pay policies and structured welfare programs. The study underscores the necessity of policy reforms to enhance employee satisfaction, ensure financial security, and foster institutional stability. The recommendations derived from this research provide actionable insights for policymakers and administrators to improve wage structures and employee welfare in Nepalese community colleges.